Crustal structure and tectonic implications of the southernmost Merida Andes, Venezuela, from wide-angle seismic data analysis. (June 2022) - Avila-García, J.; Schmitz, M.; Mortera-Gutierrez, C.; Bandy, W.; Yegres, L.; Zelt, C.; Aray-Castellano, J.; ,
Abstract: The crustal structure of the Merida Andes in southwestern Venezuela is crucial to our understanding of both, the complex regional geodynamics of the northern part of South America, as well as the development of the hydrocarbon basins located along its flanks. Symmetric and asymmetric models of the Merida Andes have been proposed based on geological and geophysical (principally gravimetric) surveys, without counting detailed structures from wide-angle seismic. This work examines the crustal structure of the southwestern part of the Merida Andes in Venezuela using controlled seismic sources along a 500 km wide-angle seismic profile (named ANDES SUR). Forward modeling is carried out to obtain a layer-based, P-wave, crustal velocity model. An alternative velocity model is obtained by applying a first arrival tomography for the upper 20 km depth, and a joint PmP and Pn inversion for the deeper crust. Important lateral P-wave velocity variations and low-velocity zones (LVZ) are observed within the upper crust. To the northwest, these lateral velocity variations are probably related to the deformation zones of Icotea and Tarra Faults, and the southeast to the Mantecal and Apure grabens. The integration of seismological data to the profile provides some clues about a possible slow-shear movement between the upper and the lower crust (brittle-ductile transition zone) at the NW end of the profile, as well as the possible northwestward incipient subduction of the South American Plate beneath the Maracaibo Triangle Block. We interpret the Boconó Fault's main trace as a take-off surface detaching from the interface between the upper and lower crust and dipping to the SE. A slight NW displaced crustal root of the Merida Andes is observed in all models, being the root ∼150 km wide with an approximately 9 km downward deflection (from ∼46 to 55 km depth) of the Moho. The crustal structure along the profile ANDES SUR, together with the observations along two profiles located further north, provide information about the tectonic implication along the strike of the Merida Andes, favoring an asymmetric model with possible NW directed South American lower crust and upper mantle underthrusting or incipient subduction beneath the Maracaibo Triangle Block beneath the center of the Merida Andes. Highlights: We identify an NW displaced crustal root beneath the northwest flank of the Merida Andes mountain belt. The Low-Velocity Zones are linked with fault and thrust fold structures within the layer-based velocity model. Joint PmP and Pn inversion was carried and an asymmetric model for the Merida Andes is supported by the velocity models. The upper crustal structure of Merida Andes is dominated by thrust folds and faults systems slightly dipping to the southeast. The velocity models highlight a SE-directed B-type subduction and an NW-directed A-Type underthrusting/subduction processes.